Application of Educational Game-Based Online Learning Media in Improving Mathematical Communication Skills - Sutio, Sutio (International Journal of Education Research and Development, 2021)
This research is motivated by the low mathematical communication skills about the material of circle elements in the second-grade students of SD Negeri Simpang Sari. This is because online teaching and learning activities are less effective and students' perceptions of the difficulty of learning Mathematics, thus making students less mathematical communication skills when learning Mathematics online. Therefore, researchers make improvements to learning using online learning media based on educational games which are expected to be a solution to the problems found. The objectives of this study are: 1) Describe the application of online learning media based on educational games in improving mathematical communication skills in second-grade students of SD Negeri Simpang Sari. 2) Describe the improvement of mathematical communication skills after the implementation of online learning media based on educational games for second-grade students of SD Negeri Simpang Sari. The classroom action research model chosen is the Kurt Lewin model which consists of two cycles with four stages in each cycle, namely planning (implementation), acting (action), observing (observing), and reflecting (reflection). Data collection techniques used are interviews, observations, tests, and virtual documentation.